Smoking-Attributable Mortality in Bangladesh : Proportional Mortality Study - Alam, Dewan S. (World Health Organization, 2015)
Smoking causes about 25% of all deaths in Bangladeshi men aged 25 to 69 years and an average loss of seven years of life per smoker. Without a substantial increase in smoking cessation rates, which are low among Bangladeshi men, smoking-attributable deaths in Bangladesh are likely to increase.